CORRELATION BETWEEN THE STUDENTS' HABIT IN LISTENING TO ENGLISH SONGS AND THEIR VOCABULARY MASTERY AT SMA NEGERI 10 PALEMBANG - Salwa Zhafirah Bernanda; Heru Setiawan; Yuyun Hendrety (Universitas Tridinanti Palembang, 2022)
The objectives of this study were to find out whether or not there was any significant correlation between students’ habit in listening to English songs and their vocabulary mastery of the eleventh graders of SMA Negeri 10 Palembang and to measure how much students’ habit in listening to English songs contributed to their vocabulary mastery. The sample of this study was 80 students taken by purposive sampling technique. The method used in this study was correlational study. The instruments to collect the data were questionnaire and test. In analyzing the data, the writers used Pearson Product Moment and regression analysis. The result of correlation analysis showed that the r-value (0.818) was higher than r-table (0.344) at the level of probability (p) significance with sig.2-tailed (0.000) was lower than the alpha value (0.05). It can be concluded that there was a significant correlation between students’ habit in listening to English songs and their vocabulary mastery. The result of regression analysis showed that value of R2 was 0.669 and p-value (0.000) was lower than α-value (0.05). It indicated students’ habit in listening English songs positively contributed to their vocabulary mastery as much 66.9%.Keywords: listening habit, English songs, vocabulary mastery